2019
DOI: 10.5186/aasfm.2019.4417
|View full text |Cite
|
Sign up to set email alerts
|

Locally convex spaces and Schur type properties

Abstract: In the main result of the paper we extend Rosenthal's characterization of Banach spaces with the Schur property by showing that for a quasi-complete locally convex space E whose separable bounded sets are metrizable the following conditions are equivalent: (1) E has the Schur property, (2) E and Ew have the same sequentially compact sets, where Ew is the space E with the weak topology, (3) E and Ew have the same compact sets, (4) E and Ew have the same countably compact sets, (5) E and Ew have the same pseudoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…If E is a locally convex space, we denote by Proof. The clauses (i)-(iii) are equivalent by Proposition 2.5, and Theorem 1.2 of [19] exactly states that (i) and (iv) are equivalent.…”
Section: The Josefson-nissenzweig Property In Locally Convex Spacesmentioning
confidence: 82%
“…If E is a locally convex space, we denote by Proof. The clauses (i)-(iii) are equivalent by Proposition 2.5, and Theorem 1.2 of [19] exactly states that (i) and (iv) are equivalent.…”
Section: The Josefson-nissenzweig Property In Locally Convex Spacesmentioning
confidence: 82%
“…Then L(X) is the direct sum of |X|-many copies of R, and hence the strong dual of L(X) is R |X| . Since R |X| has the Schur property, Proposition 3.1 of [13] implies that L(X) has the (sDP )-property.…”
Section: Proof Of Main Resultsmentioning
confidence: 99%
“…He used this result to show that every Banach space C(K) has the (DP ) property, see [18,Théorème 1]. Extending this result to locally convex spaces and following [13], we consider the following "sequential" version of the (DP ) property: an lcs E is said to have the sequential Dunford-Pettis property ((sDP ) property) if given weakly null sequences {x n } n∈N and {χ n } n∈N in E and the strong dual E ′ β of E, respectively, then lim n χ n (x n ) = 0. In [15], we showed that C p (X) has the (sDP ) property for every Tychonoff space X.…”
Section: Introductionmentioning
confidence: 99%
“…A subset A of a topological space X is called sequentially compact if every sequence in A contains a subsequence which is convergent in A. Following [21], a Tychonoff space X is sequentially angelic if a subset K of X is compact if and only if K is sequentially compact. It is clear that every angelic space is sequentially angelic.…”
Section: The (Dp ) Property and The Grothendieck Property For C P (X)mentioning
confidence: 99%
“…He used this result to show that every Banach space C(K) has the (DP ) property, see [23,Théorème 1]. Extending this result to locally convex spaces (lcs, for short) and following [21], we consider the following "sequential" version of the (DP ) property. Definition 1.2.…”
Section: Introductionmentioning
confidence: 99%